Factors Influencing Malaysian Undergraduate Students’ Intention To Use E-Recruitment - Barkat, Onika; Mohamed, Rosmah (Indonesian Scientific Publication, 2024)
Recruitment is important for organizational performance, and in recent years, employee recruitment has become a widely debated topic. Due to the technological advancement and competitiveness, the organizations are applying online recruitment. E-recruitment is the practise of recruiting jobs by means of the internet or some other electronic tools. The objective of this thesis is to investigate the influencing factors (Perceived Ease of Use, Perceived Usefulness, Concern of Privacy, Interpersonal Influence, Internet Self-efficacy) impact on the Intention to use E-Recruitment of Malaysian Undergraduate Students. Technology acceptance model (TAM) and social exchange theory (SET) used as underpinning theories. 244 responses were collected using the self-administrated questionnaires based on quantitative methodology. The study is a cross sectional in nature. Data was analysed by descriptive, correlational, regression analysis in SPSS. The findings indicated all the constructs have positive and significant relationship on the dependent variable. This study contributed to the human resource’ body of knowledge and Malaysian human resource industry. Employers, Information Technology department, policy makers as well as job seekers can get valuable insights from the findings of the study. The study can be extended by using diverse variables, intervening variables as well as in another country or population context.